Position statement on macroprolactinemia from the Department of Neuroendocrinology of the Brazilian Society of Endocrinology and Metabolism (SBEM) and the Brazilian Society of Clinical Pathology/Laboratory Medicine (SBPC/ML) - Glezer, Andrea; Elias, Paula Condé Lamparelli; Nogueira, Vania dos Santos Nunes; Garmes, Heraldo Mendes; Kasuki, Leandro; Rollin, Guilherme Alcides Flôres Soares; Martins, Manoel Ricardo Alves; Leme, Adriana Caschera; Rosa, Pedro Saddi; Naves, Luciana Ansaneli; Batista, Marcelo Cidade (Archives of Endocrinology and Metabolism, 2025)
Measurement of serum prolactin levels is a common practice in clinical settings, particularly among women of reproductive age. In cases of hyperprolactinemia, identifying macroprolactinemia can help prevent unnecessary investigation and inappropriate treatments. This Position Statement, jointly prepared by the Brazilian Society of Endocrinology and Metabolism (SBEM) and the Brazilian Society of Clinical Pathology/Laboratory Medicine (SBPC/ML), addresses several aspects of macroprolactinemia relevant to clinical practice - including concepts, definitions, epidemiological aspects, measurement techniques, and the role of screening - and discusses some clinical dilemmas.